SISTEM PENDIDIKAN DAN PENGEMBANGAN PESANTREN DALAM MEMBENTUK KEMANDIRIAN SANTRI DI PONDOK PESANTREN DARUL AMAN GOMBARA MAKASSAR - Muh. Shadiq Al Sabri; M. Hasibuddin Mahmud; Akhmad Bazith; Maryam Ismail; Hasanna Lawang; Ratika Nengsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Muh. Shadiq Al Sabri. The Education and Development System of Islamic Boarding School in Forming Students’ Independence at Pondok Pesantren Darul Aman Gombara Makassar (supervised by Dr. H. M. Hasibuddin Mahmud, SS., MA. and Dr. H. Akhmad Bazith, Lc., MA). Islamic education is one of the most essential aspects in the life of Muslims. In this context, students’ independence is a crucial element that cannot be overlooked. It plays an import ant role in shaping strong and self-reliant character, as well as preparing students to become resilient leaders in the future. This study aims to: (1) identify the educational system in forming students’ independence at Pondok Pesantren Darul Aman Gombara Makassar; and (2) examine the development system in forming students’ independence at the same institution. The research employed a descriptive qualitative method. Data were collected through observation, interviews, and documentation. The data analysis techniques included data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the system implemented at Darul Aman Gombara Islamic Boarding School in Makassar in fostering students’ independence is carried out through integrated stages of planning, implementation, guidance and habituation, as well as evaluation. In addition, the development system through student organizations, da'wah programs and speech training, as well as extracurricular activities, further strengthens students’ independence, particularly in terms of discipline, responsibility, and self-confidence. However, there are still some students who are less compliant and less active; therefore, guidance and supervision need to be improved so that students’ independence can be developed more optimally and evenly. The conclusion of this study shows that the educational and developmental system implemented at Darul Aman Gombara Islamic Boarding School in Makassar is fairly effective in fostering students’ independence through integrated implementation in daily life. This system is able to develop discipline, responsibility, and self-confidence, although there are still some students who are less compliant and less active, thus requiring further guidance.